Isolation of Phosphate Solubilizing Bacteria and their Use for Plant Growth Promotion in Tomato Seedling and Plant - Pathak, Rajiv; Paudel, Vipassana; Shrestha, Anupama; Lamichhane, Janardan; Gauchan, Dhurva. P. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Phosphorous (P) is an essential macronutrient and most soils contain high levels of P. However, its availability to plant is limited by rapid immobilization of phosphorous compounds to insoluble forms and hence plant available forms of P in soils are found in low amounts. Phosphate solubilizing bacteria provide an eco-friendly alternative to convert insoluble phosphates into plant available forms. In the present study, three phosphate solubilizing bacterial isolates (PB-1, PB-4 and VC-01) with visually significant phosphate solubilizing abilities were isolated from tomato rhizosphere soil. In-vitro study in pikovskaya’s agar revealed that isolate PB-1 had the highest phosphate solubilizing ability with a phosphate solubilizing index of 2.08±0.07 followed by isolate VC-01 (1.31±0.09) and PB-4 (1.24±0.08). Isolates were used as bacterial inoculum to assess their ability to promote tomato (Lycopersicon esculentum var. Srijana) seedling and plant growth in in-vitro and greenhouse experiment respectively. Isolate PB-4 showed best growth promotion in seedling assay whereas isolate PB-1 and VC-01 also promoted seedling growth compared to control. In greenhouse experiment however, isolates VC-01 and PB-1 significantly enhanced all parameters (shoot length, root length, shoot and root dry weight) compared to uninoculated control whereas isolate PB-4 had a positive effect on all parameters except root length.Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 2, 2017, page: 61-70